Not in a class of one’s own: The role of social origins and destinations for entry into gender-atypical fields of study - Irene Prix; Elina Kilpi-Jakonen (Turku Center for Welfare Research (TCWR), 2022)
While men’s and women’s tendency to specialize in different fields of study is well-established worldwide, little is known about the extent that such gender segregation is tied up with issues of social stratification. Drawing on Finnish register-based data of over 90,000 young people, we investigate the ways in which social background is associated with men’s and women’s gender-atypical field choices at both the level of upper secondary vocational education and two types of higher education. Findings from our linear probability models show that social origin matters for entry into gender-atypical fields. However, the direction of association varies between lower and higher levels of education, particularly in the case of men. Comparing our findings with expectations derived from socialization-based interpretations of social origin and risk aversion theory, we argue that considerations related to social class and status maintenance may be more important promotors of gender-atypical field choice than gender-egalitarian orientations.